The Moderating Effect of Gender on Overconfidence in Investment Decisions - Rosyidah Rahmah; Nugraha Nugraha; Dian Kurnianingrum; Margareth Setiawan (ARBITRASE: Journal of Economics and Accounting, 2026)
This study examined the influence of overconfidence on the investment decisions of Indonesian individual or retail investors. The research design used in this study uses quantitative survey approach. The questionnaire was distributed online using the Populix platform. The analysis used Hayes' Moderation Model 1, utilizing a quantitative survey of 500 retail investors from the Indonesia Stock Exchange (IDX). This study explored the moderating effect of gender on the relationship of overconfidence and investment decisions. The results showed that overconfidence significantly increased investment decisions, with the relationship being more pronounced in men than in women. Overconfidence positively influenced investment decisions for both genders, with a more pronounced effect on male investors, as evidenced by the conditional effect. These findings advance behavioral finance by demonstrating gender-specific effects of overconfidence in emerging markets and suggest that investor education and risk communication strategies should be tailored to demographic characteristics of investors, particularly gender, to more effectively address overconfidence bias.